SoftGirls: An Institutional Strategy at Pascual Bravo to Promote Female Inclusion in Software Engineering Education - Guerrero, Marcela (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
SoftGirls is an initiative developed within the Faculty of Engineering at the Pascual Bravo University Institution, aimed at strengthening both technical and soft skills among female students from the academic community. The objective of this article is to present the work carried out by the SoftGirls study group, which focuses on enhancing its members’ competencies in computer science, specifically in programming, UX/UI design, and emerging trends in software engineering. The study group has been active since mid 2024 and integrates in-person sessions, visits to software industry companies, talks and training courses delivered by expert professionals, as well as an institutional certification of the acquired competencies issued by the educational institution.